ANALYSIS OF THE INFLUENCE OF IMPLEMENTING INTERPROFESSIONAL COLLABORATION PRACTICE ON THE QUALITY OF INTEGRATED ANTENATAL CARE SERVICES AT PEBAYURAN BEKASI HEALTH CENTER IN 2023 - Yulastri, Siti Aisyah; Khairiah, Rahayu (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: In facing the complex health problems of patients today, health professionals are required to provide excellent and quality health services. Handling health problems requires a comprehensive and collaborative approach between professionals. Research Objective: To determine the effect of implementing Interprofessional Collaboration Practice on the quality of integrated antenatal care services at the Bekasi Pebayuran Community Health Center in 2023. Research Method: The research design used in this research is cross-sectional. with the population in this study being Health Workers at the Bekasi Pebayuran Community Health Center, totaling 40 people.